2014
DOI: 10.1186/s40359-014-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive remediation and d-cycloserine for individuals with bipolar disorder

Abstract: BackgroundCognitive remediation (CR) has shown significant promise in addressing the cognitive deficits that accompany serious mental illness. However, this intervention does not appear to completely ameliorate the cognitive deficits that accompany these illnesses. D-cycloserine (DCS), an NMDA receptor partial agonist, has been shown to enhance the therapeutic benefits of learning-based psychosocial interventions for psychiatric disorders. Thus, the goal of this study is to examine the utility of combining cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…A highly promising treatment approach is the combination of pharmacological and psychological interventions (eg, ). This is likely to produce synergistic effects on brain function that may translate into more robust efficacy on cognition and functional outcome than either treatment modality alone.…”
Section: Results: Task Force Recommendationsmentioning
confidence: 99%
“…A highly promising treatment approach is the combination of pharmacological and psychological interventions (eg, ). This is likely to produce synergistic effects on brain function that may translate into more robust efficacy on cognition and functional outcome than either treatment modality alone.…”
Section: Results: Task Force Recommendationsmentioning
confidence: 99%
“…At EPICENTER, participants received metacognitive remediation (MCR: [ 71 , 72 ])—a form of cognitive remediation shown to improve numerous domains of cognitive functioning among individuals with first-episode psychosis, including processing speed, attention/vigilance, working memory, verbal learning, visual learning, reasoning and problem-solving, and social cognition [ 71 ]. MCR involves participation in both computerized cognitive remediation exercises and metacognitive skills development exercises with a clinician.…”
Section: Methodsmentioning
confidence: 99%
“…Very little is known about the longitudinal course of cognitive deficits and the neuropsychological underpinnings of the dynamics of BD (74). Improving the knowledge on the development in time of cognitive dysfunction in BD [role of depressive episodes, role of manic episodes, role of mixed episodes, role of specific medications for better or for worse, role of cognitive remediation programs, role of inflammatory mediators (75), role of genetic factors (76,77)] would contribute to identify targets for treatment, to determine possible subtypes of the disorder, and to develop better therapeutic strategies (78,79). The metaanalytic study by Samamé et al (13) showed that cognitive deficits remain stable after a follow-up period of 4.62 years.…”
Section: Discussionmentioning
confidence: 99%